Kohlebergbau und Wasserwirtschaft als Grundlage der Entwicklung im Damodar-Gebiet - Stang, Friedrich (ERDKUNDE, 1968)
The Damodar Valley owes its position as one of the most important industrial areas of the Indian Union to its rich coal deposits which have been exploited since the railway building era in the middle of the last century. Coal mining was restricted for a long time to the best coal near the surface and was mined often with primitive methods by migrant labour. Since India’s independence, rising coal demand has led to thorough modernisation. At the same time, the industrialisation of the central Damodar Valley has made notable progress and the new iron and steel works, heavy machinery, locomotive, aluminium, and synthetic fertiliser factories, and power stations have led to the foundation of many new settlements and towns. Recent developments would however not have been possible without the improvement of water supply by a multipurpose project of the Damodar Valley Corporation. The immediate impetus for the construction of dams was provided by the flood catastrophes which time and again laid waste the lower Damodar Valley. But the energy genera tion and water supply improvements associated with these schemes have been as important for industry as the extension of irrigated area in the fertile lower course has been for feeding the growing population. The large number of tasks associated with the project, above all the agricultural reform made necessary by soil conservation and irrigation measures, have made the Damodar Valley into the first example of comprehensive regional planning in India.